Comparison of different methods for image lag investigation of indirect converting flat-panel detectors - Hofmann, Th.; Burtzlaff, S.; Voland, V.; Salamon, M.; Nachtrab, Frank; Sukowski, F.; Uhlmann, N. (Nuclear Instruments and Methods in Physics Research Section A: Accelerators, Spectrometers, Detectors and Associated Equipment, 2009)
To measure the origins and dependencies of image lag in indirect converting flat-panel detectors, different methods were implemented. According to ASTM E 2597-07, the detector will be irradiated for a defined period with a constant flux. Then shutting off the tube, one can determine the image lag by monitoring the detector signal. We developed a different method, using a triggered shutter, to enable exactly defined illumination of the detector. Integration times longer than 1 s allow an exposure only during the delay time of the detector. This way, comparable results for image lag for decreasing intensity can be obtained. To investigate the image lag for increasing intensity, the triggered shutter stays open. By opening the shutter for more than one frame, then closing, it is possible to observe the build-up and decay of the image lag in dependence on the illumination time. Using these methods image lag was investigated with respect to irradiation intensity, time, incident X-ray spectrum, gain capacity of the detector and lag homogeneity of the detector surface.
EAM Import::2019-03-13

Comparison of different sources for laboratory X-ray microscopy - Ebensperger, T.; Stahlhut, P.; Nachtrab, Frank; Zabler, S.; Hanke, Randolf (Journal of Instrumentation, 2012)
This paper describes the setup of two different solutions for laboratory X-ray microscopy working with geometric magnification. One setup uses thin-film transmission targets with an optimized tungsten-layer thickness and the electron gun and optics of an electron probe micro analyzer to generate a very small X-ray source. The other setup is based on a scanning electron microscope and uses microstructured reflection targets. We also describe the structuring process for these targets. In both cases we show that resolutions of 100 nm can be achieved. Also the possibilities of computed tomography for 3D imaging are explored and we show first imaging examples of high-absorption as well as low-absorption specimens to demonstrate the capabilities of the setups.
EAM Import::2019-03-13

Multi-Energy X-ray Imaging as a Quantitative Method for Materials Characterization - Firsching, M.; Nachtrab, Frank; Uhlmann, N.; Hanke, R. (Advanced Materials, 2011)
X-ray imaging is an established tool for materials characterization even though it usually has the drawback of not being a quantitative method. This drawback can be overcome by energy-sensitive X-ray imaging methods such as the basis material decomposition method presented in this paper, which can provide quantitative results for materials characterization.
EAM Import::2019-03-12

Quantitative material analysis by dual-energy computed tomography for industrial NDT applications - Nachtrab, Frank; Weis, S.; Kessling, P.; Sukowski, F.; Hassler, U.; Fuchs, T.; Uhlmann, N.; Hanke, R. (Nuclear Instruments and Methods in Physics Research Section A: Accelerators, Spectrometers, Detectors and Associated Equipment, 2011)
Dual-energy computed tomography (DECT) is an established method in the field of medical CT to obtain quantitative information on a material of interest instead of mean attenuation coefficients only. In the field of industrial X-ray imaging dual-energy techniques have been used to solve special problems on a case-by-case basis rather than as a standard tool. Our goal is to develop an easy-to-use dual-energy solution that can be handled by the average industrial operator without the need for a specialist. We are aiming at providing dual-energy CT as a measurement tool for those cases where qualitative images are not enough and one needs additional quantitative information (e.g. mass density extgreekr and atomic number Z) about the sample at hand. Our solution is based on an algorithm proposed by Heismann et al. (2003) [1] for application in medical CT . As input data this algorithm needs two CT data sets, one with low (LE) and one with high effective energy (HE). A first order linearization is applied to the raw data, and two volumes are reconstructed thereafter. The dual-energy analysis is done voxel by voxel, using a pre-calculated function F(Z) that implies the parameters of the low and high energy measurement (such as tube voltage, filtration and detector sensitivity). As a result, two volume data sets are obtained, one providing information about the mass density extgreekr in each voxel, the other providing the effective atomic number Z of the material therein. One main difference between medical and industrial CT is that the range of materials that can be contained in a sample is much wider and can cover the whole range of elements, from hydrogen to uranium. Heismann's algorithm is limited to the range of elements Z=1–30, because for Z>30 the function F(Z) as given by Heismann is not a bijective function anymore. While this still seems very suitable for medical application, it is not enough to cover the complete range of industrial applications. We therefore investigated the possibilities of extending the afore mentioned approach to dual-energy imaging to a wider range of materials.
EAM Import::2019-03-13

Setup of an electron probe micro analyzer for highest resolution radioscopy - Hanke, R.; Nachtrab, Frank; Burtzlaff, S.; Voland, V.; Uhlmann, N.; Porsch, F.; Johansson, W. (Nuclear Instruments and Methods in Physics Research Section A: Accelerators, Spectrometers, Detectors and Associated Equipment, 2009)
Structural investigation and characterization of objects below the micrometer-scale level often require either big efforts in experimental setup and critical time schedules as is the case with synchrotron sources or a big effort in test object preparation including destructive methods (e.g. grinding) for the investigation within an electron microscope. The limiting factor for high-resolution imaging with conventional X-ray sources is the focal spot size of the X-ray tube used. Focal spot sizes down to 500 nm can be achieved with double-focusing X-ray tubes and transmission targets. To be able to use X-ray transmission imaging for structural investigation with highest resolution in everybody's laboratory, we modified an electron probe micro analyzer (EPMA) to be used as an X-ray source. With this it is possible to obtain electron beam diameters below 200 nm and to produce X-rays using a special transmission target. Due to the low X-ray intensity and in order to profit from the high magnification, a high-resolution, low-noise detector is to be used. We chose a Medipix2 detector for that purpose. We will present the setup and first results of radioscopic images with a resolution of about 240 nm.
EAM Import::2019-03-13

Simple solutions for spectroscopic, photon counting X-ray imaging detectors - Nachtrab, Frank; Hofmann, T.; Firsching, M.; Uhlmann, N.; Hanke, R. (Nuclear Science Symposium Conference Record (NSS/MIC), 2009)
The central idea of our approach is to use standard imaging sensors for industrial optical imaging as X-ray sensors. We use them as a simple solution for a spectroscopic, single photon counting X-ray detector with a reduction of the pixel size by a factor of almost 10 compared to commercially available photon counting X-ray detectors. In principle, each of the sensors photodiodes can act as a direct converting X-ray sensor pixel. We compare the acquisition of images in integrating and photon-counting mode and notice a much better spatial resolution in photon-counting mode compared to integrating- mode. Using the benefits of direct detection we gather spectroscopic information of the incident photons. Gray value and energy deposition are correlated linearly. Energy resolutions down to 700 eV are by limitation to single event clusters. Furthermore detection efficiency, multiplicity, DQE(0), MTF and the radiation hardness are investigated.
EAM Import::2019-03-13

X-ray dynamic defectoscopy utilizing digital image correlation - Jandejsek, Ivan; Nachtrab, Frank; Uhlmann, Norman; Vavrik, Daniel (Nuclear Instruments and Methods in Physics Research Section A: Accelerators, Spectrometers, Detectors and Associated Equipment, 2010)
This paper presents the utilization of the image processing technique known as digital image correlation for X-ray dynamic defectoscopy purpose. Digital image correlation is a non-contact technique (optical or X-ray) that provides full-field and high resolution measurement of deformation fields within an object subjected to loading. In this case it was used for crack detection in a bar specimen subjected to tension loading.
EAM Import::2019-03-12